(untitled) - Hastings, Alan (New York, 1997)
One principle guiding this book is that the material covered here is essential for any graduate student in ecology or population biology and ecology are short changed if they are not given the opportunity to work through and understand the mathematical models which have become a core part of our discipline.
Keywords: Population biology,Sinh thái học quần thể; Mathematical models,Mô hình toán học